A usability evaluation of Job Street for elderly system (JSES) / Amira Bahiah Mohamad - Mohamad, Amira Bahiah (2017)
Despite the fact that elderly should enjoy their retirement after their long work after so many years, there are still some elderly who opt to instead continue working past their retirement age due to several reasons. Those who choose to continue working made the decision mostly due the insufficient savings which could be caused by poor financial planning causing insufficient retirement funds, possibly exorbitant lifestyle, or even due to the bad financial market during their retirement age. However, as the need rise for elderly to jump back into the workforce, there is still a lack of opportune platforms that the elderly can utilize in getting back into the working environment that is suitable for their paces. In this research, an existing job recruitment website called Job Street for Elderly System (JSES) which was previously developed by a UiTM undergraduate student is evaluated to determine its usability. Five consenting elderly participants were asked to participate in the usability evaluation. The data collection was firstly performed using demographic survey form which was initially distributed to primarily determine that the correct targeted sampling group is gathered as the sampling was collected purposively to target the elderly age group of 60 years old and above, followed by usability testing sessions with each participant by asking them to complete a set of task scenarios with observer supervising the sessions and taking notes on the comments voiced out loud by the participants using Think Aloud protocol. Finally, a U.S.A.B.I.L.I.T.Y. survey form is distributed containing several usability components that allows the participants to determine the usability of JSES prototype from their experience with JSES interface earlier. Data from these sessions are then analyzed qualitatively. The findings indicated that the website is generally considered as a usable website that can be implemented for the use of elderly in their search for job vacancies based on its fulfillment to the usability components presented in the U.S.A.B.I.L.I.T.Y. survey questions.